High Psychiatric Morbidity and Comorbidity Among Female Prisoners in Hunan, China - Zhong, Shaoling; Zhu, Xiaomin; Chen, Yanan; Guo, Huijuan; Luo, Chenyuli; Liang, Xiaoxi; Wang, Fanglan; Chen, Hui; Zhou, Jiansong; Wang, Xiaoping (Frontiers in Psychiatry, 2020)
Background: High prevalence of mental disorders has been found among female prisoners in Western countries, however little is known about the epidemiology of mental disorders in such populations in China. This study aims to investigate psychiatric morbidity and comorbidity among sentenced prisoners in a female prison in China. Methods: A cluster sample of 2703 female adult prisoners from Hunan Provincial Female Prison were interviewed with the Mini International Neuropsychiatric Interview, a semi-structured Diagnostic and Statistical Manual of Mental Disorders 4th edition (DSM-IV) mental disorder diagnostic tool. The rates of psychotic disorder, mood disorder, anxiety disorder and substance use disorder were reported. Results: Nearly 2/3 (66.2%, N=1790) of the sample fulfilled the criteria for at least one lifetime DSM-IV disorder: 36.5% had major depression, 22.2% had post-traumatic stress disorder (PTSD), and 16.5% had drug use disorder. Drug use disorders were the major comorbid disorders, that 60.8% of people with alcohol use disorder and 37.0% of those with psychotic disorders also had a drug use disorder. More than one-quarter (26.1%) met criteria for a current diagnosis of any mental disorder, of which major depression was the most common. Conclusion: The high levels of psychiatric morbidity and comorbidity in a representative sample of female prisoners in China indicate a significant burden, and potentially unmet needs that require identification and therapeutic intervention in this setting.